1966
DOI: 10.1002/pol.1966.150040620
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of inorganic salts with poly(ethylene oxide)

Abstract: SynopsisEvidence is presented for the interaction of metal salts such as potassium iodide with polyethers such as poly(ethy1ene oxide). This interaction is sufficiently marked that the incorporation of 10-3001, of the salt in the bulk polymer markedly reduces crystallinity while retaining compatibility. Examination of electroviscons effects in methanol demonstrates that the salt-polymer adduct behaves as a typical polyelectrolyte a t low salt concentrations, while the polymer in absence of salt is essentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
2
2

Year Published

1971
1971
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(68 citation statements)
references
References 9 publications
7
57
2
2
Order By: Relevance
“…The Hoechst booklet [26] classifies the ether oxygen of PEO as a Lewis base and it forms complexes with acids and phenols. It was found that there is an interaction between PEO and poly (sodium acrylate) [27], PEO and iodide ion [28] and a binding between ether oxygen of PEO and chloride ion [5,6]. Nevertheless, data collected from viscometric measurements of PEO in salt solutions [29] and from Top values show that it is not possible to have such bindings of the ions used in this study and the ether oxygen of PEO with the exception of I-and Br-.…”
Section: Discussioncontrasting
confidence: 50%
“…The Hoechst booklet [26] classifies the ether oxygen of PEO as a Lewis base and it forms complexes with acids and phenols. It was found that there is an interaction between PEO and poly (sodium acrylate) [27], PEO and iodide ion [28] and a binding between ether oxygen of PEO and chloride ion [5,6]. Nevertheless, data collected from viscometric measurements of PEO in salt solutions [29] and from Top values show that it is not possible to have such bindings of the ions used in this study and the ether oxygen of PEO with the exception of I-and Br-.…”
Section: Discussioncontrasting
confidence: 50%
“…A higher negative charge of niosome formulations containing PEG was observed. This may be due to an effect of a higher concentration of sodium ion in the system as mentioned above since there are observations of the interaction of metal salts to polyethylene glycol previously reported (Lundberg, Bailaey, & Callard, 1966;Dzhumadilov, Ismagulova, Bekturov, & Rafikov, 1989). As the formulation became more complex, the variation in changes of zetapotential was reduced to a range of −70 mV to −80 mV.…”
Section: Niosome Characterizationmentioning
confidence: 83%
“…Some authors 26 studying the binding of electrolytes to poly(ethylwith two and three, respectively, adjacent ionic groups on the macroion, to form intrachain bridene oxide) in aqueous solutions have established that the anions are actually bound with the polyges leading to an additional folding of the polyion and hence to a more decreased viscosity. Neverether through an ion-dipole interaction, whereas the other ones 27,28 have shown that binding is detheless, the viscosity decrease is less pronounced at greater salt concentrations.…”
Section: It Is Well Known That the Hydration Degree Of The Ions Incmentioning
confidence: 99%